PNAS nexus - National Academy of Sciences (U.S.) (Oxford University Press on behalf of the National Academy of Sciences, 2022)
'PNAS Nexus' is a broad, highly selective, open access journal with a focus on innovation and rapid publication across the biological, medical, physical, engineering, social, and political sciences.
Keywords: Science : Periodicals; Science; Medicine